2013
DOI: 10.1186/1471-2164-14-s2-s3
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-target prediction based on transcriptional regulation

Abstract: BackgroundmicroRNAs (miRNAs) are tiny endogenous RNAs that have been discovered in animals and plants, and direct the post-transcriptional regulation of target mRNAs for degradation or translational repression via binding to the 3'UTRs and the coding exons. To gain insight into the biological role of miRNAs, it is essential to identify the full repertoire of mRNA targets (target genes). A number of computer programs have been developed for miRNA-target prediction. These programs essentially focus on potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
(27 reference statements)
1
20
0
Order By: Relevance
“…From the circRNA-miRNA coexpression network, we observed that the four axes were combined with the four circRNAs (hsa_circRNA_100375, hsa_circRNA_400082, hsa_circRNA_102034 and hsa_circRNA_101319, respectively). MiRNAs always negatively regulate their target genes [45][46][47]. To identify the key pathway in the four miRNA axes, we used the miRTarBase software implemented in CluePedia of Cytoscape to predict the miRNA target genes [48] and used ClueGo to predict the KEGG pathway.…”
Section: Discussionmentioning
confidence: 99%
“…From the circRNA-miRNA coexpression network, we observed that the four axes were combined with the four circRNAs (hsa_circRNA_100375, hsa_circRNA_400082, hsa_circRNA_102034 and hsa_circRNA_101319, respectively). MiRNAs always negatively regulate their target genes [45][46][47]. To identify the key pathway in the four miRNA axes, we used the miRTarBase software implemented in CluePedia of Cytoscape to predict the miRNA target genes [48] and used ClueGo to predict the KEGG pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Current target prediction algorithms rely on canonical binding through seed (nt 2–8 from the 5′ end) complementarity (reviewed in ). The experimentally verified success rate of these algorithms ranges from 18% to 70%, depending on predicted target function, illustrating a desperate need for improved miR target isolation and validation methods . In addition, the predictions do not take into account the relative amount of each target gene and their degree of suppression or other non‐canonical targets, such as the open reading frame and 5′ ends of protein coding genes and non‐coding RNAs.…”
Section: Micrornasmentioning
confidence: 99%
“…The experimentally verified success rate of these algorithms ranges from 18% to 70%, depending on predicted target function, illustrating a desperate need for improved miR target isolation and validation methods. 38 In addition, the predictions do not take into account the relative amount of each target gene and their degree of suppression or other non-canonical targets,…”
Section: Micrornasmentioning
confidence: 99%
“…As described in article S3 of this supplement [32], Toyofumi Fujiwara (INTEC) introduced a novel method for predicting miRNA targets, based on the hypothesis that promoters of miRNAs and their targets tend to share (predicted) cis-elements [32]. In a highlights talk, Michal Linial (The Hebrew University of Jerusalem) discussed a novel algorithm, miRror2.0, which enables the discovery of combinatorial regulation of transcription by several miRNAs [33].…”
Section: Systems Biology Transcription and Expression Regulationmentioning
confidence: 99%